2009
DOI: 10.1021/jp907054h
|View full text |Cite
|
Sign up to set email alerts
|

Study of Carbon Dioxide Adsorption on Mesoporous Aminopropylsilane-Functionalized Silica and Titania Combining Microcalorimetry and in Situ Infrared Spectroscopy

Abstract: Two calcined mesoporous supports, silica and titania, were functionalized with aminopropylsilane (APS). The samples were characterized using ATR (attenuated total reflectance), nitrogen sorption at 77 K, and thermogravimetric analysis. The functionalized silica and titania are mesoporous and were grafted with 1.4 and 1.6 molecules of APS per nm 2 , respectively. Infrared measurements propose that the properties of the amine sites are affected by the chemical properties of the support. For example, the NH 2 ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
261
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(282 citation statements)
references
References 51 publications
20
261
0
1
Order By: Relevance
“…Differential molar adsorption heats of the various samples are reported in Please do not adjust margins Please do not adjust margins Figure 11(B ) and S6(B) (for very low coverages) as a function of the adsorbed amounts. These values are in agreement with the data reported in the literature for similar systems 58,59 . For what concerns the A--SBA--15 material, the adsorption enthalpy starts at very high values (higher than --90 KJ mol --1 ; zero--coverage differential heat of adsorption qo ~ --120 KJ mol --1 ) and this suggests the presence of a small fraction of extremely energetic sites, i.e.…”
Section: Study Of the Co 2 Capture Capacitysupporting
confidence: 93%
“…Differential molar adsorption heats of the various samples are reported in Please do not adjust margins Please do not adjust margins Figure 11(B ) and S6(B) (for very low coverages) as a function of the adsorbed amounts. These values are in agreement with the data reported in the literature for similar systems 58,59 . For what concerns the A--SBA--15 material, the adsorption enthalpy starts at very high values (higher than --90 KJ mol --1 ; zero--coverage differential heat of adsorption qo ~ --120 KJ mol --1 ) and this suggests the presence of a small fraction of extremely energetic sites, i.e.…”
Section: Study Of the Co 2 Capture Capacitysupporting
confidence: 93%
“…The development of this model stems from earlier observations regarding the interactions of CO 2 with amine-grafted mesoporous silica under dry and humid conditions [13]. The data indicated that in the presence of dry gaseous feed, CO 2 interacts chemically with amine groups with a maximum CO 2 /N ratio of 0.5, consistent with the formation of carbamate species, an observation that has been corroborated by other groups using infrared spectroscopy [14,15]. In addition, CO 2 can also adsorb physically on the surface of the material, particularly at pressures beyond 0.05 bar at room temperature.…”
Section: Introductionsupporting
confidence: 54%
“…The absorbance spectra reveal an additional band at 1680 cm À1 , which can be assigned to C=O stretching for carbamic acid. [15] A small increase in the intensity of the peaks in the 3750 cm À1 region along with those in 3500 cm À1 in Figure 1 [6b, [15][16] Switching the flow from CO 2 /H 2 O/air to Ar caused the CO 2 MS intensity to sharply drop, to a baseline level. The corresponding spectra (iii) and (iiiÀi) in Figure 1 b and c show a larger decrease in the NH 2 ÀO band intensity than the carboxylate and carbamate band intensities, further confirming the presence of two different types of species:…”
Section: Introductionmentioning
confidence: 99%